The Development of Sets Worksheets for Junior High School Students Growing Process Skill and Scientific Attitude - Wita Setianingsih; Putri Anjarsari; Widodo Setiyo Wibowo; Astri Novitasari (Universitas Negeri Yogyakarta, 2018)
The aims of this research are to produce SETS worksheet that can be applied in teaching learning to grow and process skills and scientific attitude for students in Junior High Shcool. The study was a Research and Development (RnD) with students in class VIII SMP N 1 Sewon Bantul as a subject of study. The reseach start form July to November 2015. The study began with a literatature study and field study to obtain information about the problem faced at school, and followed by planning, drafting and validating product by experts. The result shows that SETS worksheet feasible to use in teaching and learning based on the validation result from lecturer, teacher and student response. The SETS Worksheet potential for growing the student's process skills and the scientific attitudeAbstract english version, written using Time New Roman-11, italic. Abstract contain research aim/purpose, method, and reseach results; written in 1 paragraph, single space among rows, using past tense sentences.